KELAINAN PADA TEMPORO MANDIBULAR JOINT (TMJ) - suhartini, suhartini (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2011)
Mastication movement is interaction of some component, such as teeth, mastication musclary, and temporomandibular joint/ TMJ. TMJ is connective joint between mandible and maxilla. In its function, TMJ need teeth and musculary that worked integrally and sinergitic. Tooth missing case, especially in posterior region, can cause disordes in mastication movement, and finally it caused TMJ disorder.